Role of Sukuk al-Istisna’ in the economic development of Islamic capital - Issoufou, Chaibou (Opción, 2019)
This paper examines the legality of Istisna’ contract, similarities and dissimilarities between Istisna’ contract and Salam as well as Ijarah via a qualitative method which is based on the view of prominent Muslim scholars. As a result, Istisna contract, in general, is a vital contract which can contribute a significant role in the economic development of a country. In conclusion, Sukuk al-Istisna is the crucial element of financing a project which will be carried out in the future as the issuer of Sukuk al-Istisna’ can conclude a parallel Istisna’ contract on an asset which will be manufactured in the future.